1967
DOI: 10.1139/m67-011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of Lysostaphin in Experimental Staphylococcal Infections

Abstract: When tested in three experimental staphylococcal infections—acute peritonitis in mice, mouse leg edema produced by a localized infection, and dermal rabbit ear infections—lysostaphin demonstrated in vivo chemotherapeutic activity. Doses of less than 0.007 mg/kg (intraperitoneally) and 0.5 mg/kg (subcutaneously) of lysostaphin prevented death in 50% of the mice with acute staphylococcal peritonitis. A single intramuscular dose (0.15 mg/mouse) of lysostaphin suppressed the swelling produced by the injection of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The continuing emergence of antibiotic-resistant S. aureus infections (4,16,37) has spurred the need for new antimicrobial agents to treat these infections. Previous studies from the 1960s and 1970s demonstrated that lysostaphin is a potent anti-staphylococcal agent and has potential as a therapeutic agent against S. aureus infections (10,13,14,32,33,36,45). Study of lysostaphin as an anti-staphylococcal agent was discontinued, however, due to lack of homogeneous preparations of lysostaphin and the availability of other effective antibiotic treatments.…”
mentioning
confidence: 99%
“…The continuing emergence of antibiotic-resistant S. aureus infections (4,16,37) has spurred the need for new antimicrobial agents to treat these infections. Previous studies from the 1960s and 1970s demonstrated that lysostaphin is a potent anti-staphylococcal agent and has potential as a therapeutic agent against S. aureus infections (10,13,14,32,33,36,45). Study of lysostaphin as an anti-staphylococcal agent was discontinued, however, due to lack of homogeneous preparations of lysostaphin and the availability of other effective antibiotic treatments.…”
mentioning
confidence: 99%
“…The beneficial effect of lysostaphin has been demonstrated in numerous studies (13,16,17,31,38). Recently, it was shown to effectively eradicate oxacillin-resistant and vancomycin-intermediate-susceptible S. aureus strains in a rabbit model of endocarditis (8,28), and its ability to kill methicillin-resistant S. aureus (MRSA) has been demonstrated in rabbit models of both keratitis (9,11) and endophthalmitis (10,11).…”
mentioning
confidence: 99%
“…Earlier studies in animal models of oxacillin-susceptible S. aureus-induced infection indicated that lysostaphin was an effective treatment agent against intraperitoneal infection and renal abscess models in mice and against experimental aortic valve endocarditis in dogs caused by a penicillinase-producing S. aureus strain (3,10,14,15,16,19,(24)(25)(26)(27)32). Though there was evidence of efficacy, the impurity of lysostaphin preparations and wide availability of alternative antistaphylococcal antibiotics halted further development of lysostaphin as a therapeutic agent.…”
mentioning
confidence: 99%